A Contrastive Study of the Translator’s Behaviour in English and Spanish Translations of Metaphors in Xi Jinping: The Governance of China - Chang, Jiang; Ying, Luo (Sinología hispánica. China Studies Review, 2024)
This study examines the English and Spanish translations of metaphors in Xi Jinping: The Governance of China (I-III) within the theoretical framework of Translator Behavior Criticism. In the description of the translators’ behavioral tendencies and diachronic changes, differences are identified between the English and Spanish translating teams with regards to their philosophy of translation, which leads to an analysis of the social motivations of the translators’ behaviors within the field of political discourse translation in China. The following findings have been derived: 1) The Spanish translation is faithful to the form of expression of the ST, which suggests a translators’ behavioral tendency towards the “truth-seeking” principle. The English translation is freer since it upholds a semantic rather than formal equivalence to the ST, suggesting that the English translating team is more oriented towards the “utility-attaining” principle than their Spanish counterparts. 2) Observed from a diachronic perspective, the English translating team always maintained a balance between the two above-mentioned principles in translating the metaphors and their “truth-seeking” and “utility-attaining” behaviors were both enhanced in their translation of the third volume. The Spanish translating team always tilted towards the “truth-seeking” principle, demonstrating just a slight increase of “utility-attaining” behavior throughout their translation of the three volumes. 3) There is an evident difference between the English and Spanish translating teams regarding their “philosophy of faithfulness”. A “semantic” faithfulness with pragmatic concerns advocated by the former team is becoming the mainstream norm governing the current field of political discourse translation in China.